How macroeconomic performance affects farmer’s term of trade: Evidence from East Java Province, Indonesia - Qodri, Lutfi Asnan; Ismail, Munawar; Ekawaty, Marlina; Wahyudi, Setyo Tri (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
This paper attempts to show that causality of the impact of macroeconomic factors in the form of inflation and gross domestic product on the farmer term of trade in East Java Province, Indonesia. This research was carried out over eleven years quarterly, starting from 2010-2021, and was analyzed using the Vector Error Correction Model (VECM). The finding of this study indicated that, in the short and long term, inflation has a negative impact but not a significant effect. A 1% increase in inflation in the current period would have the impact of decreasing the term of trade of farmers by 0.0009% in the future period. This often happens due to the decline in the value of the currency which is mostly caused by speculator buyers who buy products from farmers. Meanwhile, a 1% increase in gross regional domestic product in the current period would have an increase in the farmer term of trade by 0.02% in the next period. This finding shows that inflation cannot be seen as extraordinary, affecting to the farmer’s term of trade. Rising inflation can lead to the decreasing level of farmers' welfare due to costs that must be paid by farmers.JEL Classification E31; J43; O11